Circulating extracellular vesicle-containing microRNAs reveal potential pathogenesis of Alzheimer’s disease - Wang, Yi; Yuan, Ping; Ding, Lu; Zhu, Jie; Qi, Xinrui; Zhang, Yanyan; Li, Yunxia; Xia, Xiaohuan; Zheng, Jialin C. (Frontiers in Cellular Neuroscience, 2022)
The pathogenesis of AD remains unknown till today, hindering the research and development of AD therapeutics and diagnostics. Circulating extracellular vesicles (EVs) can be utilized as a new window to spy upon AD pathogenesis. Altered microRNA profiles were noted in both the cerebrospinal fluid (CSF)- and blood-isolated EVs of AD patients, implying for outstanding potential of circulating EV-containing miRNAs (CEmiRs) to serve as important regulators in AD pathogenesis. Although several CEmiRs were found to play a part in AD, the association of globally altered miRNA profiles in patients’ serum-derived EVs with AD pathogenesis remains unclear. In this study, we firstly investigated the miRNAs profile in serum-derived EVs from AD, mild cognitive impairment (MCI) patients, and health individuals. We observed differential expression patterns of CEmiRs and classified them into ten clusters. We identified the predicted targets of these differentially expressed CEmiRs (DECEmiRs), and analyzed their biological functions and interactions. Our study revealed the temporal regulation of complex and precise signaling networks on AD pathogenesis, shedding light on the development of novel therapeutic strategies including multi-target drug combination for AD treatment.